Public Sector Strategy Design: Theory and Practice for Government and Nonprofit Organizations - McNabb, David E.; Lee, Chung-Shing (Routledge, 2021)
Within the public sector, strategies are not designed to influence markets, but instead to guide operations within a complex environment of multilateral power, influence, bargaining, and voting. In this book, authors David McNabb and Chung-Shingh Lee examine five frameworks public sector organization managers have followed when designing public sector strategies. Its purpose is to serve as a guide for managers and administrators of large and small public organizations and agencies. This book is the product of a combined more than 60 years of researching, teaching, and leading organizational seminars on the theory and practice of management applications in industrial, commercial, nonprofit, and public sector organizations. The book consists of four parts: Strategic Management and Strategy Fundamentals; Frameworks for Designing Strategies; Public Sector Strategies; and Implementing Strategic Management. Throughout, the focus is on the widespread value of strategic management and adopting the strategy appropriate for the organization. Including chapters on game theory, competitive forces, resources-based view, dynamic capabilities, and network governance, the authors demonstrate ways that real managers of public sector and civil society organizations have put strategic management to work in their organizations. This book will be of interest to both practicing and aspiring public servants.